Early Renoprotective Effect of Ruxolitinib in a Rat Model of Diabetic Nephropathy - Mohamed M. El-Kady; Reham A. Naggar; Maha Guimei; Iman M. Talaat; Olfat G. Shaker; Maha Saber-Ayad (MDPI AG, 2021)
Diabetic kidney disease (DKD) is still one of the unresolved major complications of diabetes mellitus, which leads ultimately to end-stage renal disease in both type 1 and type 2 diabetes patients. Available drugs that suppress the renin-angiotensin system have partially minimized the disease impact. Yet, there is an unmet need for new therapeutic interventions to protect the kidneys of diabetic patients. In DN, glomerular sclerosis and tubulointerstitial fibrosis are mediated through several pathways, of which JAK/STAT is a key one. The current study explored the potential renoprotective effect of the JAK1/JAK2 inhibitor ruxolitinib (at doses of 0.44, 2.2, and 4.4 mg·kg−1) compared to that of enalapril at a dose of 10 mg·kg−1, in a rat model of streptozotocin-induced diabetes mellitus over 8 weeks. The effect of ruxolitinib was assessed by determining urinary albumin/creatinine ratio, serum level of cystatin, and levels of TGF-β1, NF-κB, and TNF-α in renal tissue homogenates by biochemical assays, the glomerular sclerosis and tubulointerstitial fibrosis scores by histological analysis, and fibronectin, TGF-β1, and Vimentin levels by immunohistochemical staining with the respective antibodies. Our results revealed a significant early favorable effect of a two-week ruxolitinib treatment on the renal function, supported by a decline in the proinflammatory biomarkers of DKD. This pre-clinical study suggests that the renoprotective effect of ruxolitinib in the long term should be investigated in animals, as this drug may prove to be a potential option for the treatment of diabetic kidney disease.